Exploring attitudes toward taxation of sugar-sweetened beverages in rural Michigan - Andrea E. Bombak; Taylor E. Colotti; Dolapo Raji; Natalie D. Riediger (BMC, 2021)
Abstract Background While policies to address "obesity" have existed for decades, they have commonly focused on behavioral interventions. More recently, the taxation of sugar-sweetened beverages is gaining traction globally. This study sought to explore individuals' attitudes and beliefs about sugar-sweetened beverages being taxed in a rural Michigan setting. Methods This qualitative study was conducted using critical policy analysis. Data were collected in 25 semi-structured, audio-recorded interviews with adult Michiganders. Following data collection, transcripts were coded into themes using NVivo software. Results Four themes emerged in participants' perspectives regarding sugar-sweetened beverages being taxed: resistance, unfamiliarity, tax effects, and need for education. While some participants were unfamiliar with sugar-sweetened beverage taxes, many viewed taxation as a "slippery slope" of government intervention, which invoked feelings of mistrust. In addition, participants predicted a sugar-sweetened beverage tax would be ineffective at reducing intake, particularly among regular consumers, who were frequently perceived as mostly low income and/or of higher weight. Conclusions Further research is needed to explore perceptions of sugar-sweetened beverage taxes in different geographic areas in the USA to examine how perceptions vary. Policymakers should be aware of the potential implications of this health policy with respect to government trust and stigma towards lower income and higher-weight individuals.